소세포 폐암의 분류 및 치료를 위한 방법 및 시스템 - PARK ELIZABETH M; GAY CARL M; HEYMACH JOHN V; BYERS LAUREN A (2023)
본 개시내용의 측면은 소세포 폐암 (small cell lung cancer; SCLC)을 분류 및 치료하기 위한 방법을 지시한다. 특정 측면은 세포 표면 단백질을 위한 표적화 제제를 사용하는 SCLC를 갖는 대상자의 치료에 관한 것이고, 여기서, 표적화 제제는 SCLC의 하위유형 분류를 기초로 하여 선택된다. SCLC 하위유형 (예를 들면, SCLC-A, SCLC-N, SCLC-P, SCLC-I)을 갖는 대상자를 확인하고, 확인된 SCLC 하위유형과 연관된 세포 표면 단백질을 표적화하기 위해 구성된 표적화 제제를 투여하는 방법이 개시된다. 또한 SCLC의 치료를 위한 표적화 제제를 포함하는 조성물이 개시된다. Aspects of the present disclosure are directed to methods for classification and treatment of small cell lung cancer (SCLC). Certain aspects pertain to treatment of a subject having SCLC using a targeting agent for a cell surface protein, where a targeting agent is selected based on a subtype classification of the SCLC. Disclosed are methods for identifying a subject as having an SCLC subtype (e.g., SCLC-A, SCLC-N, SCLC-P, SCLC-I) and administering a targeting agent configured to target a cell surface protein associated with the identified SCLC subtype. Also disclosed are compositions comprising targeting agents for treatment of SCLC.